Advanced biomaterials and biodevices - Tiwari, Ashutosh, 1978-; Nordin, Anis N. (Wiley ; Scrivener Publishing LLC, 2014)
"This book is devoted to all of the emerging areas of biomaterials and biodevices, including therapeutic agents, molecular targeting, and diagnostic imaging capabilities. The authors provide a comprehensive view of cutting-edge research on advanced materials for healthcare technology and applications. The book is written for scientists, researchers, and clinicians from diverse backgrounds across chemistry, physics, materials science and engineering, medical science, pharmacy, biotechnology, and biomedical engineering"--Resumé vydavatel
Keywords: biologické materiály; nanostruktury; biological materials; nanostructures; elektronické knihy; sborníky; electronic books; papers of several authors